POTENCY OF THE CHININDO (CHINA, INDIA, AND INDONESIA) AS WORLD ECONOMY DYNAMISM AND ITS INFLUENCE TO REGIONAL ECONOMIC STABILITY - Mohamad Hery Saripudin, Mansur Juned , (Jurnal Mandala, 2018)
In general, China, India and Indonesia (Chinindo) have great potential to lead economic growth in Asia and the world. It can be seen from high production growth rate of China and India and high production rate of input goods and energy sources from Indonesia. Moreover, the population of these three countries is very great and is able to make the three countries to maintain economic activities with the support of domestic demand. In other words, it reduces vulnerability to the shock of the world economy. The three countries also have ability to supply goods with relatively low prices and a factor that supports it is low costs of manpower. The research tries to explain how the potential of the three countries to be the moving motor of the world economy and to study the cooperation dynamics in the three countreis and their influence to economic stability in each region.